A Literature Review On the Formulation, Characterization, and Stability of Cinnamomum burmannii Emulgel Extract as an Antioxidant and Sunscreen - Rodhia Ulfa; Ferdy Firmansyah; Fenny Khairunnisa; Putri Lestari (Universitas Wahid Hasyim Semarang, 2024)
Emulgel is a pharmaceutical formulation that integrates the characteristics of both emulsions and gels, resulting in a semisolid product. The utilization of emulgel formulations has been shown to enhance the efficacy of drug delivery by facilitating deeper skin penetration and subsequently augmenting its pharmacological activity. The antioxidant and sunscreen properties of cinnamon bark extract make it suitable for incorporation into an emulgel formulation. Variations in the concentration of extracts and gelling agents can have an impact on the physical properties, stability, and pharmacological efficacy of the emulgel. The objective of this review is to ascertain the optimal concentrations of extracts and gelling agents in emulgel formulations for enhanced efficacy. The employed methodology entails conducting a comprehensive review of scholarly articles pertaining to emulgel formulations containing cinnamon bark extract. These formulations encompass a range of concentrations of both the extract itself and gelling agents, while also possessing antioxidant and sunscreen properties. The formulation that is recommended is one that satisfies the criteria pertaining to its physical attributes, stability, and pharmacological efficacy. The emulgel formulation that best meets the specified criteria consists of a 1% concentration of cinnamon bark extract in combination with the gelling agent Viscolam MAC 5%.